Management of change vis-à-vis organizational productivity - Oga, Chery May M. (2016)
This study aimed to look into the management of change in Jose Rizal Memorial State University System in relation to the organizational productivity. This study utilized the descriptive-correlational method of research. Data Mining and data analysis were conducted in obtaining the data on the organizational productivity in Jose Rizal Memorial State University. The respondents of the study were the department heads and staff in the different administrative offices of Jose Rizal Memorial State University System. The data was collected to the said offices and was treated accordingly. A modified questionnaire was used in gathering data from the offices to answer questions regarding management of change and organizational productivity of Jose Rizal Memorial State University. The administrative heads and administrative staff’s ratings on the management of change among administrative heads was comparable as to understanding the environment, developing a vision for the change, planning the change and management, communication skills, leading others through change and personal resilience. On the other hand, the rating of administrative heads and administrative staff on management of change of administrative heads vary significantly as to consulting and involving others. The overall performance of Jose Rizal Memorial State University System was very satisfactory in the SUC’s Leveling. It was found out that management of change has a very high correlation to organization productivity of JRMSU System.
Keywords: Jose Rizal Memorial State University; Mindanao studies; State universities and colleges; Management of change